Performance of Magnetic Resonance Imaging-based Permeability Indices for Preoperative Glioma Grading. - Alikhani, Sina; Zakariaee, Seyed Salman (Journal of Basic Research in Medical Sciences, 2026)
Introduction: Due to the inherent limitations of histopathology as the gold standard method for glioma grading, in recent years, alternative methods, including methods based on imaging data, have been proposed for better glioma grading. This study aimed to determine the performance of permeability parameters (Ktrans, Kep, Ve, and Vp) quantified using the dynamic contrast-enhanced MRI (DCE-MRI) method for preoperative glioma grading. Materials & Mediods: The radiological data of 31 patients with pathologically confirmed gliomas were retrospectively reviewed. The permeability parameters, including Ktrans, Kep, Ve, and Vp, were quantified using DCE-MRI data. The Mann-Whitney U test was used to assess the significance of differences in these parameters between different grades of glioma. The performance of the parameters for glioma grading was evaluated using receiver operating characteristic (ROC) curve analysis. Results: The mean age of the patients was 39.2 ± 14.1 years, and 18 of the participants were males (58.06%). Ktrans, Kep, and Vp parameters demonstrated a significant difference between different grades of glioma. The results showed that Ktrans yielded the best grading performance compared to other studied parameters (AUC>71%). Vp, Kep, and Ve parameters ranked next. Conclusion: DCE-MRI provides valuable quantitative parameters that can reliably differentiate between glioma grades. These noninvasive imaging biomarkers can serve as a powerful complement to the standard histopathological grading system, guiding better treatment planning and preventing unnecessary interventions.